Extractivismo aurífero, poder local y conflictos territoriales : Comparación de cuatro casos en México y Colombia - Roldán Zarazo, Daniel Santiago (2025)
Comparative case analysis at the territorial scale has been rarely applied to the study of extractivism in Latin America, limiting the identification of its nuances and diversity. This research contributes to the debate through the reconstruction and comparative analysis of four large-scale gold mining cases: Temixco and San José del Progreso in Mexico, and Santurbán and Buriticá in Colombia). These cases, marked by protracted and at times violent conflicts, reveal trajectories that do not follow a linear pattern but rather recurrent cycles of escalation and de-escalation. The analysis, grounded in a relational conception of the State, integrates four dimensions: protest cycles, political opportunity structures, organizational structures, and discursive frames. Findings show that the cohesion or fragmentation of local elites, the ability to forge broad, cross-class alliances, and the construction of powerful empty signifiers shape resistance effectiveness. Theoretically, the study challenges methodological individualism and economism, which reduce social actors and movements to agents driven by material self-interest or individual utility maximization. It argues that extractive disputes in social movements are constituted through the interplay between material conditions and symbolic constructions. Methodologically, the research incorporates a comparative analysis of local political opportunity structures, accounting for a “territorial gap” between national policies and their regional impact.